Effect of Vertical Stretching on the Extraction of Mean Identity From Faces. (September 2017) - Bagaïni, Alexandra; Hole, Graham
Observers can extract the mean identity from a set of faces and falsely recognise it as a genuine set member. The current experiment demonstrated that this 'perceptual averaging' also occurs with vertically stretched faces. On each trial, participants decided whether a target face was present in a preceding set of four faces. In the control condition, the faces were all normally proportioned; in the stretched set condition, the face sets were stretched but the targets were normal; and in the stretched target condition, the face sets were normal but the targets were stretched. In all three conditions, participants falsely identified the set mean as a face that had been presented within the set, implying that this identity-averaging effect is based on high-level identity information rather than the low-level physical characteristics of the face stimuli.